penentuan lokasi pusat camilan khas madura - kemal, ariq; cahyono, hendry (Universitas Negeri Surabaya, 2024)
Abstract Small business problems are generally related to managerial skills or unprofessional management. This is because existing knowledge is very limited. These issues include capital, productivity, human resources, technology, competitiveness, innovation, and marketing issues. Another classic and very fundamental problem facing SMEs is their ability to compete with both small and large companies alike. The inability of SMEs to compete in both domestic and global markets is influenced by many factors. One is the lack of access and opportunity to market. Starting from these issues, the purpose of this study is to determine the central location of typical Maduranian snacks. I found that it was in From this we can conclude that Pamekasan is a very suitable place for Madura.typical snack SMEs compared to Sampang and Sumenep whose interaction value is lower than Pamekasan. Keywords: SMEs in Madura, Madura Economic Growth. Gravity Analysis